Secretory cells in Etlingera elatior (Jack) R. M. Smith (Zingiberaceae): morphology, histochemistry, and essential oil composition - Lee, Yee-Ling; Abas, Faridah; Ismail, Intan Safinar; Ding, Phebe (Universiti Putra Malaysia, 2025)
Etlingera elatior is a perennial, aromatic herb with attractive flavour and fragrance afforded by organic compounds that are stored and released from specialised structures; however, the secretory structures remain undefined. Thus, this study was carried out to determine the secretory cells in the leaves, inflorescences, and peduncles of E. elatior by using scanning electron and light microscopies. Histochemical tests were performed to localise and ascertain the nature of secretion materials, while gas chromatography-mass spectrometry was used to characterise the composition of essential oils (EO). Findings indicate the presence of a heterogeneous mixture comprising EO, mucilaginous and/or lipophilic substances in the secretory cells. A total of 50 compounds were identified in the EO, with the predominance of alcohol. The presence of several terpenic compounds (α-pinene, (E, E)α-farnesene, (E)-caryophyllene, E-β-farnesene, (E)-nerolidol) suggests a potential involvement of the secretory structures in plant signalling. The widespread distribution of secretory cells throughout the plant tissues indicates adaptive features of the plant’s secretory system. These cells emerged as the main secretory system of E. elatior that renders the EO.